Development of Augmented Reality Learning System Based on Kolb's Experimential Learning Model - Rasim Rasim; Seni Siti Inayah; Yudi Ahmad Hambali; Eka Fitrajaya Rahman; Dwi Novia Al Husaeni (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2026)
Students’ learning motivation often decreases when the learning method does not align with their individual learning styles, posing a challenge for effective and meaningful education. Augmented Reality (AR) technology offers an interactive solution to increase student engagement. This study aims to develop an AR-based learning system adapted to Kolb’s learning styles: Diverger, Assimilator, Converger, and Accommodator, to support personalized and enjoyable learning. The system was developed using the ADDIE model and an object-oriented approach. Evaluation involved black box testing and user testing based on the Technology Ac-ceptance Model (TAM). Results showed over 80% of students were satisfied with the application, 75% found learning more interesting, and approximately 70% demonstrated increased active participation. TAM analysis revealed an average score of 80.26 and a positive correlation between perceived ease of use and motivation. The application encourages deeper exploration of material and boosts students’ confidence in facing academ-ic challenges. In conclusion, the developed system effectively supports technology-based personalized learn-ing. Its implication suggests that AR integration in education can enhance learning quality and serve as a foundation for future intelligent systems incorporating artificial intelligence.